From micro to macro: how occupational complexity influences cognitive function after retirement at different scales - Chua, Hui Wen (Nanyang Technological University, 2024)
As the population ages, understanding the factors that contribute to cognitive aging becomes ever more paramount in informing strategies to promote cognitive health. While much scholarly attention has been given to lifestyle factors and individual characteristics, occupational factors remain relatively unexplored. Given that the majority of adulthood is typically spent working, occupational factors, such as occupational complexity, ought to play a role in influencing one’s cognition, extending to post-retirement. Hence, our study aims to explore the relationship between cognitive aging and occupational complexity, introducing a multi-scalar framework with micro, meso and macro level of analysis. Grounded in the cognitive reserve hypothesis, we explored how engagement in intellectually stimulating occupations shape cognitive reserves and subsequently influences cognitive trajectories post-retirement. At the micro-level, individual cognitive processes, such as problem-solving and decision-making, are examined. The meso-level analysis then dives into social organising, collaboration and social engagement on cognitive reserve accumulation. Lastly, at the macro-level, we discuss factors such as culture and structure. By introducing a multi-scalar perspective in reviewing occupational complexity beyond a single scale, our paper provides a novel comprehensive view that enables the examination of potential interactions between the different levels. This adds value to the existing cognitive literature and could be used to develop targeted strategies to navigate occupational complexity at each level and its influences on cognitive functioning after retirement